2016
DOI: 10.1371/journal.pone.0147056
|View full text |Cite
|
Sign up to set email alerts
|

Higher Caffeinated Coffee Intake Is Associated with Reduced Malignant Melanoma Risk: A Meta-Analysis Study

Abstract: BackgroundSeveral epidemiological studies have determined the associations between coffee intake level and skin cancer risk; however, the results were not yet conclusive. Herein, we conducted a systematic review and meta-analysis of the cohort and case-control studies for the association between coffee intake level and malignant melanoma (MM) risk.MethodsStudies were identified through searching the PubMed and MEDLINE databases (to November, 2015). Study-specific risk estimates were pooled under the random-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 45 publications
5
17
0
Order By: Relevance
“…Increased consumption of tea and coffee, two of the most popular beverages worldwide, has been associated with decreased risk of cancers of several sites in human studies. [1][2][3][4][5][6][7][8][9][10] Less is known about the association between tea or coffee consumption and risk of glioma, a cancer for which few lifestyle factors have been identified. 11,12 Coffee is a rich source of caffeine, and both tea and coffee contain additional biologically active compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Increased consumption of tea and coffee, two of the most popular beverages worldwide, has been associated with decreased risk of cancers of several sites in human studies. [1][2][3][4][5][6][7][8][9][10] Less is known about the association between tea or coffee consumption and risk of glioma, a cancer for which few lifestyle factors have been identified. 11,12 Coffee is a rich source of caffeine, and both tea and coffee contain additional biologically active compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] POTENTIAL ANTI-CARCINOGENIC EFFECTS OF CAFFEINE There is a growing literature indicating that caffeine may protect against melanoma and non-melanoma skin cancers. [14][15][16][17][18][19][20][21][22][23][24][25][26] In coffee, although there are other potential anticancer ingredients other than caffeine, caffeine is one of the mostly researched compounds in chemopreventive power of coffee. Caffeine exerts its antiproliferative and anti-carcinogenic action via regulating cell growth, development and apoptosis.…”
Section: The Major Compound Of Coffee: Caffeinementioning
confidence: 99%
“…Caffeine modulates cell cycle and increases UV-induced apoptosis through p53dependent and p53-independent biological pathways. Data from recent studies have revealed an inhibitory effect of caffeine on the proliferation of both melanoma and nonmelanoma cell lines [14][15][16][17][18][19][20][21][22][23][24][25][26].…”
mentioning
confidence: 99%
“…Several scientific studies on animal models and humans highlight the cancer preventive potential of phytochemicals [6][7][8][9][10]. Coffee is the most widely consumed beverages in the world and has been reported to have significant anticarcinogenic effects [11][12][13].…”
Section: Introductionmentioning
confidence: 99%